2007
DOI: 10.1007/s10620-007-9757-9
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Response of HCV Genotype 1 to Consensus Interferon and Ribavirin Versus Pegylated Interferon and Ribavirin

Abstract: Achieving an antiviral response at a reasonable cost is a challenge in the treatment of patients with chronic hepatitis C. A previous study indicated that consensus interferon with ribavirin had promising activity against hepatitis C virus (HCV) genotype 1. The objective of this study was to determine the virologic response with consensus interferon or pegylated interferon alpha-2b plus weight-ribavirin in patients chronically infected with HCV genotype 1. Intention-to-treat analysis showed response in 37% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…The results represent a three to sixfold improvement over the results achieved in prior non-responders utilizing a second course of peg-IFN [4][5][6][7][8][9] and confirm the results of others, who have used c-IFN [24][25][26][27][28][29][30][31][32]. The results are even more noteworthy in that 81% of the patients had a genotype 1 infection, 21% had cirrhosis, and 24% were African American at the initiation of their therapy, factors known to reduce response rates significantly.…”
Section: Discussionsupporting
confidence: 83%
“…The results represent a three to sixfold improvement over the results achieved in prior non-responders utilizing a second course of peg-IFN [4][5][6][7][8][9] and confirm the results of others, who have used c-IFN [24][25][26][27][28][29][30][31][32]. The results are even more noteworthy in that 81% of the patients had a genotype 1 infection, 21% had cirrhosis, and 24% were African American at the initiation of their therapy, factors known to reduce response rates significantly.…”
Section: Discussionsupporting
confidence: 83%
“…Initially, the rate of sustained viral response (SVR) was about 10% [28] . After ribavirin and pegylated-interferon became available, the rate of SVR reached 40-50% [29] . These interferon-based antiviral therapies have been shown to reduce the incidence of HCC in patients with SVR [30] .…”
mentioning
confidence: 99%
“…Although one recent study revealed that CIFN 3 times weekly in combination with weight-based RBV may be as effective as combination PEG IFN alfa-2b and weight-based RBV in the treatment of HCV genotype 1 patients, comparative data are limited. 32 Therefore CIFN is not considered the standard of care for naïve patients with chronic HCV infection.…”
Section: Consensus Interferon In Naïve Patients With Chronic Hepatitis Cmentioning
confidence: 99%